Coats of Arms in the Lithuanian Metrica in the Grand Duchy of Lithuania in the 16th Century - Sipavičiūtė, Justina (Lietuvos istorijos studijos, 2024)
The aim of this article is to analyse the way coats of arms were described in the Lithuanian Metrica. This article takes a deep look at the circumstances that led to the mention of a coat of arms in the Lithuanian Metrica. Was it important for a nobleman of that time to name their coat of arms, and what was depicted on it? And if so, how detailed was its description? Published and unpublished books of the Lithuanian Metrica have revealed a lot of important material about coats of arms. The research has shown that the largest part of the Lithuanian Metrica is made up of files where coats of arms appear on stamps or signets. In case stamps or signets were lost, their owners would be in a hurry to report their disappearance as soon as possible, but most often they could not describe the stamp accurately; at best, they would state that the stamp or signet bore just their coat of arms or their personal coat of arms. No more details would be provided. A smaller proportion of the Lithuanian Metrica not only contains accurate indications of coats of arms depicted on the stamps/signets, but also provides the titles of specific coats of arms. Privileges of bachelorhood that are described in the books of the Lithuanian Metrica are one of the most comprehensive sources describing not just the coats of arms but their colours as well. The files of the Lithuanian Metrica show that women used their father’s coat of arms in their stamps. As we can see in several files of the Lithuanian Metrica, the scribes would occasionally redraw the coats of arms. It was not uncommon for coats of arms to become subjects of disputes in court in case their authenticity was contested.